Who Gets to Farm? Agricultural Renewal, Quotas, and the Governance of Alternative Food Networks in Quebec - Mundler, Patrick; Ubertino, Simone (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2022)
In Canada, chicken, turkey, egg, and milk production is regulated through a supply management system. As a result, any Canadian farmer wishing to raise poultry or produce eggs or milk is legally required to hold a production quota. However, quota prices have risen sharply over time, creating considerable entry barriers for small farmers interested in selling supply-managed specialty products directly to consumers. The impact of the current system on small-scale farming and alternative food networks has led to growing calls for reform. In our study, we examine the debate around quota policies in the province of Quebec from a governance perspective. Our findings indicate that stakeholders disagree on the potential impact that supply management reforms would have on market stability, equity, farmer professionalism, and food safety. Fundamentally, these various points of contention highlight an underlying struggle for power and legitimacy between established stakeholders and beginning farmers, with both sides holding opposing views about the nature of farming, product quality, and sectoral management. The debate also underscores the challenges that supply-managed sectors face in trying to accommodate beginning farmers from diverse social and professional backgrounds.